2018
DOI: 10.1113/jp275558
|View full text |Cite
|
Sign up to set email alerts
|

Smoke‐induced neuromuscular junction degeneration precedes the fibre type shift and atrophy in chronic obstructive pulmonary disease

Abstract: A neurological basis for the fast fibre shift and atrophy seen in limb muscle of patients with chronic obstructive pulmonary disease (COPD) has not been considered previously. The objective of our study was: (1) to determine if denervation contributes to fast fibre shift and muscle atrophy in COPD; and (2) to assess using a preclinical smoking mouse model whether chronic tobacco smoke (TS) exposure could initiate denervation by causing neuromuscular junction (NMJ) degeneration. Vastus lateralis muscle biopsies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 82 publications
(163 reference statements)
2
57
1
Order By: Relevance
“…These changes were accompanied by reductions in RTD, both absolute and relative to peak torque, reflecting a shift towards slower contractile properties in the intact limb. This is in contrast to the results of short-term disuse studies in both healthy control subjects and pathological populations, which have reported a shift towards faster contractile properties owing to a greater expression of fast-contracting myosin heavy-chain (MHC) isoforms (Bamman et al, 1998;Kapchinsky et al, 2018;Trappe et al, 2004). The results of the present study therefore provide new evidence that changes in intrinsic contractile properties with longterm disuse are more characteristic of ageing muscle, which also displays a slowing of the contractile properties (Roos, Rice, Connelly, & Vandervoort, 1999).…”
Section: Intrinsic Contractile Propertiescontrasting
confidence: 99%
“…These changes were accompanied by reductions in RTD, both absolute and relative to peak torque, reflecting a shift towards slower contractile properties in the intact limb. This is in contrast to the results of short-term disuse studies in both healthy control subjects and pathological populations, which have reported a shift towards faster contractile properties owing to a greater expression of fast-contracting myosin heavy-chain (MHC) isoforms (Bamman et al, 1998;Kapchinsky et al, 2018;Trappe et al, 2004). The results of the present study therefore provide new evidence that changes in intrinsic contractile properties with longterm disuse are more characteristic of ageing muscle, which also displays a slowing of the contractile properties (Roos, Rice, Connelly, & Vandervoort, 1999).…”
Section: Intrinsic Contractile Propertiescontrasting
confidence: 99%
“…In contrast, this slow-to-fast shift in fiber type is not found in the VL muscle from subjects with mild-to-moderate COPD (Doucet et al, 2004 ), while this transition does not seem to exist in upper peripheral muscles such as the deltoid muscle (Gea et al, 2001 ). Several factors have been proposed to explain the skeletal muscle dysfunction in COPD, such as muscle deconditioning and reduced physical activity, neuromuscular degeneration, systemic oxidative stress and inflammation, exacerbated catabolism, hormonal disturbance, smoking, nutritional status, pharmacological treatments, aging, or gas exchange abnormalities (Gea et al, 2013 ; Kapchinsky et al, 2018 ). However, it remains extremely difficult to identify which factor(s) is/are responsible for the alteration of fiber typing.…”
Section: Adaptation Of Skeletal Muscle Fiber Type Under Conditions Ofmentioning
confidence: 99%
“…C-terminal agrin fragment-22 (CAF22) is a smaller fragment of CAFs and its circulating levels are associated with the NMJ degeneration and muscle defect in sarcopenia [ 13 ] and other catabolic conditions due to heart failure and stroke [ 14 , 15 ]. However, the association of plasma CAF22 with muscle wasting in the respiratory diseases is not well recognized despite the evidence that smoking and other conditions of lung injury can result in the destabilization of NMJs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%